Click, Trust, and Eat: Understanding How Value Shapes Purchase Intentions in Food Delivery Apps - Yans Fithratul Islamy; Nurdhina Arifa (Universitas muhammadiyah malang, 2025)
The rapid development of food delivery applications has altered consumer purchasing decisions, highlighting the significance of informational and economic indicators in influencing user behavior. This study examines the impact of online reviews and product pricing on perceived value and, in turn, purchase intention, with trust analyzed as a moderating variable. Data were gathered from 150 users of a prominent food delivery company in Indonesia and analyzed utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that online reviews and product pricing substantially elevate perceived value, thereby influencing purchase intention positively. The purchase value mediates the relationship between both antecedents and buy intention, highlighting its crucial role in customer decision-making. Nonetheless, trust did not substantially reduce the impact of perceived value on purchase intention, indicating that in markets with already elevated baseline trust, value-oriented methods may exert greater influence than trust-enhancing initiatives. These findings enhance digital consumer behavior research by affirming perceived value as a pivotal mechanism and provide actionable insights for platform operators to emphasize transparent review systems and competitive pricing.